Parliamentary Decree No. 1 of the Year 2016 On the Non Adoption of Decree Law No. 18 of the year 2015 Promulgating the Civil Service Law and Approval of its Enforceability Till 20/1/2016 - egypt (2025)
Parliamentary Decree No. 1 of the Year 2016 On the Non Adoption of Decree Law No. 18 of the year 2015 Promulgating the Civil Service Law and Approval of its Enforceability till 20/1/2016 – قرار مجلس النواب رقم 1 لسنة 2016 بعدم إقرار القرار بقانون رقم 18 لسنة 2015 بإصدار قانون الخدمة المدنية واعتماد نفاذه حتى 20/1/2016